Penerapan Model Regresi Data Panel: Determinan PDRB Sektor Unggulan di Provinsi Riau Tahun 2015-2019 - Ali Imran Mansyur; Agung Priyo Utomo (Politeknik Statistika STIS, 2021)
The economic components consist of several sectors, each sector contributes differently. Lot of sectors made it necessary to do analysis to overview the leading economic sectors whose potential can be increased to improve the economy of Riau Province. This study aims to find out the leading sector in Riau Province and provide the overview and variables that affect the regional income of the leading sector in Riau Province in 2015-2019. With overlay analysis, which is a combination of Location Quotient Analysis and Capital Ratio Analysis, the leading sectors in Riau Province are agricultural and manufacturing sectors. By using Panel data regression with fixed effect model, the result shows that agricultural labor force, agricultural sector inflation, and agricultural land area have a significant effect, while the road length has no significant effect on the GDP of agricultural sector. Meanwhile, manufacturing labor force, manufacturing sector inflation and the number of establishment have a significant effect, while the road length has no significant effect on the GDP of manufacturing sector in Riau Province in 2015-2019.